Patellar Maltracking as a Cause of Lameness in Two Dachshunds - Treharne, David Rhys; Burton, Neil James (VCOT Open, 2018)
Two Dachshunds were presented for the complaint of intermittent unilateral pelvic limb skipping lameness. Clinical examination and radiographs did not reveal any abnormalities. Computed tomography (CT) imaging showed changes in the femoropatellar joint space in both dogs and surgical evaluation revealed femoral trochlear and patellar cartilage loss. Patellar maltracking without patellar luxation or instability was diagnosed. Patellar maltracking should be included as a differential diagnosis for pelvic limb lameness in this breed.
Keywords: patellar maltracking; dachshund; chondromalacia patellae